The removal of template from SBA-15 samples synthesized from different silica sources - Yilmaz, Muge Sari; Piskin, Sabriye (SPRINGER, 2015)
Mesoporous SBA-15 was synthesized from tetraethyl orthosilicate and sodium silicate as pure silica sources and waste gold mine treatment sludge as an alternative silica source. The synthesis of SBA-15 samples were carried out by the hydrothermal method using the silica source and Pluronic P123 triblock copolymer as the structural template in an acidic medium. The synthesized materials were characterized by X-ray diffraction and nitrogen adsorption-desorption analysis. Thermal decomposition behaviors and kinetics of template from as-synthesized SBA-15 samples derived from different silica sources were investigated by thermogravimetry. The activation energies to decomposition of the template from as-synthesized SBA-15 samples were determined by Vyazovkin model-free method. The decomposition behavior of SBA-15 synthesized from waste was similar to SBA-15 synthesized from tetraethyl orthosilicate. Thermogravimetry coupled with Fourier transform infrared spectrometry analysis was applied for analysis of gaseous products evolved during thermal decomposition of synthesized samples. H2O, CO2, CH2, and CH3 were the main gaseous products released.
Keywords: SBA-15; Waste; Template removal; TG-FTIR; Model-free method; MESOPOROUS SILICA; KINETIC-ANALYSIS; SURFACTANT; ADSORPTION; EXTRACTION; COPOLYMER; TRIBLOCK; MCM-41; CALCINATION; STABILITY; Thermodynamics; Chemistry